Improving Dental and Oral Health through Counseling and Training on Dental and Oral Health Maintenance and Introduction of Dental Radiography Examination in Children and Installation of Sinks at Belawan Islamic Junior High School, Medan Belawan District - Manja, Cek Dara; Kartika, Dewi; Sitanggang, Maria NH; Astrina, Ika (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2023)
Healthy behavior can affect the health of everyone's body. Dental and oral health is very important to always pay attention to because it is part of general health. To keep your teeth and mouth healthy, you can always keep your teeth and mouth clean every day. The easiest thing to do is to brush your teeth and wash your hands before eating. Techniques and the correct way of brushing teeth greatly affect dental hygiene. If the oral health is not good, then it requires a dental radiographic examination as a supporting examination to be able to determine the condition of the teeth and the supporting tissues of the teeth as a whole. This activity is based on the need to maintain dental and oral health from an early age, so that good behavior in maintaining health can be accustomed from childhood. In addition, there are still many children in junior high school who are not properly aware of the importance of dental health for general health. This counseling can increase knowledge and provide understanding and awareness about the importance of maintaining personal and oral health by brushing teeth regularly and washing hands properly.